(untitled) (American Journal of Islam and Society, 1997)
Before delving into the subject of the role of Muslim intellectuals, we should agree on what we mean when using the term. The meaning of the word Muslim is well-known because it has been defined in the Qur’an itself. According to Sfirut ul-Nisi, verse 125, a Muslim is someone “who submits his whole self to Allah, does what is good, and follows the way of Ibrahim.” And according to verse 136 of the same sfiruh a Muslim is he who believes “in Allah, and His messengers, and the scriptures which He has sent down to those before.” Finally, Sfirut ul-Tuwbah says in verse 7 1 that believing Muslims “order what is right and forbid what is wrong, observe their prayers, pay zakat, and obey Allah and His messenger.” The meaning of the word intellectual is more difficult to determine and is not defined in the Qur’an. In fact, this term has been used only since the late 19th century. For our purposes, I do not propose to define as intellectual everybody who is “cultured” or academically trained-in Arabic al-muthaqifin. Rather, I should like to restrict the term to what is called in Arabic al-mufuqirfin: analytical minds who communicate, as opinion leaders, through lecturing or publishing and do not just sit at home, thinking and criticizing. So we know what, or who, a Muslim intellectual is. But do such individuals exist? It is well known that the so-called elite of Europe, also of Kemalist Turkey, came to believe that there was a contradiction between being intelligent and believing in God. In fact, from the middle of the 19th century to the present time, considered it Western and Turkish academics considered it intellectually chic to be an agnostic or an atheist, in particular if one was a leftist-as if intellectualism was a privilege of the Left, and not to be found on the conservative Right. This attitude, still pervasive today, goes back to the so-called Age of Reason and the Enlightenment-budding with Descartes in the 17th ...